Effects of baicalein on pancreatic cancer stem cells via modulation of sonic Hedgehog pathway. (25th April 2018) - Song, Libin; Chen, Xiangyuan; Wang, Peng; Gao, Song; Qu, Chao; Liu, Luming
Abstract: Recent studies have suggested that sonic Hedgehog (Shh) signaling pathway is aberrantly activated in cancer stem cells (CSCs). A seven-herb Chinese medicinal formula composed of Amorphophallus rivieri Durieu, Oldenlandia diffusa (Wild) Roxb, Scutellaria barbata D. Don, Gynostemma pentaphyllum (Thunb.) Mak and Amomum cardamomum L, i.e. Qingyihuaji (QYHJ) formula, has been shown to inhibit proliferation of pancreatic CSCs by inhibiting Shh signaling pathway and thereby prolong the overall survival of pancreatic cancer patients. Mass spectrometry analysis revealed that baicalein is one of the major compounds of QYHJ formula. The objective of this study was to investigate the role of Shh pathway in pancreatic cancer and to examine the molecular mechanisms of baicalein involved in pancreatic cancer treatment. We examined the effects of baicalein on pancreatic CSCs both in vivo and in vitro . The results indicated that baicalein attenuated the pluripotency of pancreatic CSCs. Then, we investigated the underlying mechanism and found that nuclear transcription factors, such as Sox-2 and Oct-4 as well as members in Shh signaling pathway, e.g. SHH, SMO, and Gli-2, were downregulated after baicalein treatment. Furthermore, silencing Gli-2 expression by small interfering RNA decreased Sox-2 expression and blocked the inhibitory effects of baicalein, suggesting that the effects of baicalein may be mediated through inhibition of Shh pathway. Our results suggested that baicalein, an active compound in QYHJ formula, could suppress the self-renewal of pancreatic CSCs through inhibition of Shh signaling pathway.